Developing New Information Sheets for Evacuees and Evacuation Centers to be Used During All Natural Disaster Phases. Issue 6 (15th December 2020) - Kitano, Hiroyuki; Kako, Mayumi; Tsuga, Kazuhiro; Nikawa, Hiroki; Mikami, Yukio; Yamashita, Hidehisa; Mori, Minako; Ohge, Hiroki
Abstract: Introduction: Evacuees' quality of life can be improved by investigating both their health problems and the conditions of evacuation centers during natural disasters. Study Objective: This study aims to develop new evacuee and evacuation center information sheets that focus on infection control, oral health and dentures, mental health, and rehabilitation during natural disasters. Methods: The analysis was conducted with the Delphi method by questioning doctors from various fields (infectious disease, psychiatry, rehabilitation, and dentistry) about the information that may be needed for evacuees and in the evacuation center environment. Results: Two information sheets were created in this study. One is an evacuation center environmental health assessment sheet that includes information about the overview of evacuees' health and the evacuation center environment. The other is an evacuee registration sheet that would be completed by the evacuees themselves. Conclusion: The information sheets developed in this study will be useful in times of disaster because they have the potential to improve evacuee health conditions, as well as evacuation center environments.